An Unusual Complication of Acute Necrotising Pancreatitis Detected by Endoscopic Ultrasound - Rana, Surinder S; Sharma, Vishal; Sharma, Ravi; Bhasin, Deepak K (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Power Doppler showing vascularity in collection.